Asymptomatic Pharyngeal Carriage of Kingella kingae Among Young Children in Vancouver, British Columbia, Canada. Issue 10 (October 2019) - Masud, Shazia; Greenman, Janet; Mulpuri, Kishore; Hasan, Mohammad R.; Goldfarb, David M.; Tilley, Peter; Gadkar, Vijay J.; Al-Rawahi, Ghada N.
Abstract : Background: Kingella kingae has emerged as a significant cause of osteoarticular infections in young children. Pharyngeal colonization is considered a prerequisite for invasive K. kingae infection. We conducted a prospective study to estimate the prevalence of pharyngeal carriage of K. kingae among healthy young children in Vancouver. Methods: From March 2016 to May 2017, children between 6 and 48 months of age visiting British Columbia Children's Hospital outpatient clinics for noninfectious causes were included in the study. Another set of participants was enrolled from a day-care center located at British Columbia Children's Hospital. A single-throat swab was collected after obtaining consent from parent/guardian. The samples were stored at −70°C and tested using an in-house developed real-time polymerase chain reaction assay. Epidemiologic characteristics and risk factors for K. kingae colonization were collected via a study questionnaire. Results: A total of 179 children were enrolled in the study, but only 174 samples were eligible for testing. Of the 174 samples, 5 had indeterminate results and the remaining 169 samples were negative by K. kingae polymerase chain reaction. The median age of participants was 23 months. About 36% of children were attending day care and had another sibling <5 years of age. Previous history of cold symptoms and antibiotic use was reported in 42% and 12%, respectively. Conclusions: The results of our study showed no prevalence of asymptomatic pharyngeal carriage of K. kingae in young children in Vancouver. Additional multicenter studies may help to understand the differences in pharyngeal carriage rate among healthy children. Abstract : Supplemental Digital Content is available in the text.